The heart of the valley a public relations plan communicating the tourism identity of the Municipality of Nabunturan - Cahigas, Edmar Gwen T. (2023)
The Philippines is known for its tourism ? destinations, sites, culture, people, language, and hospitality. The tourism industry in the Philippines contributes to the national income. Given this, each town in the country offers a distinct tourism identity. The towns devise ways of promoting their distinct tourism identities and tourist destinations. Nabunturan, the capital town of Davao de Oro, capitalizes on its tourism identity in its local talents and culture because of its lack of promising natural destinations. However, culture and the arts are rich in the town, as it cultivates artists, produces various art forms, and is vibrant in culture. Through this study, it was revealed through key-informant interview and document review that the Center of Culture and Arts is the tourism identity of the municipality. They have established the tagline ?The HeART of the Valley? to encompass being the Center of Culture and Arts. They have different tourism components under the culture and arts circuit. However, the public does not know well about this tourism identity as shown in the quantitative data. Therefore, there is an existing image gap between the municipal tourism office and the public?s perception towards Nabunturan tourism. The office utilizes a tourism marketing plan to communicate and promote Nabunturan tourism, however it is too general that it lacks specific actions in how to properly communicate their tourism identity. To address the image gap and to effectively communicate the tourism identity, the researcher developed a public relations plan in order to establish the town?s tourism identity and communicate it to the public. Various public relations activities such as media relations, social media posting, social mobilization programs were laid out as public relations tactics to establish and communicate Nabunturan?s tourism identity.